Hubungan Motivasi Belajar dan Kesiapan Belajar Peserta Didik Paket C di SKB Mojoagung - Panggalih, Satrio Bagus; Mardliyah, Sjafiatul (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
Learning readiness is the initial stage of a learning activity that encourages a person to be ready to respond or answer to themselves in a certain way to face a condition in achieving a goal. Learning motivation is the ability that a learner has after receiving a learning experience. Motivation to learn is basically a change in behavior that can be obtained from the learning process. There is a low learning motivation, especially UNPK subjects in Package C SKB Mojoagung students. This study was conducted at SKB Mojoagung offline from the target set by the researcher was achieved by adjusting the schedule of teaching and learning activities. This study uses a descriptive quantitative approach. This approach the data will be analyzed quantitatively by using sta to test the hypothesis that has been prepared. The type of research used in this study is a cross sectional approach. There is a positive and significant relationship between learning readiness and learning motivation. This means that the greater the motivation of students and readiness to learn, the students will be encouraged to respond positively in the learning process and improve their abilities so as to affect learning outcomes for the better. Readiness to learn and motivation to learn have a positive and significant relationship. This is indicated by a significance value of 0.000 0.05.